Potensi dan Pemanfaatan Tanaman Sagu (Metroxylon sp) sebagai Pangan Lokal: Studi Kasus di Desa Feruni, Kecamatan Aru Selatan, Kabupaten Kepulauan Aru - Lawalata, Imelda Jeanette; Madubun, Elia Leonard; Deraukin, Adelina; Tomasoa, Reny (Fakultas Pertanian, Universitas Pattimura, 2025)
The research was carried out in Feruni Village, South Aru District, Aru Islands Regency, from September to November 2021. This study aims to determine the potential and utilization of sago plants (Metroylon sp) in Feruni Village, South Aru District, Aru Islands Regency. The method used was a survey, and field data was collected by using questionnaires and FGD. Twenty respondents of sago’s farmers were randomly selected, and data obtained were descriptively and quantitatively processed to calculate density, frequency, dominance, and the important value index. The results showed that there are 3 types of sago in Feruni Village, South Aru District, Aru Islands Regency, namely Molat Sago (Metroxylon sagus Rottb), Tuni (Metroxylon rumphii Mart.), and Ihur (Metroxylon sylvestre Mart.). Traditional tools such as axes and machetes are used by people in Feruni village to harvest sago after putting it into the gutter, while sago leaves are used for roofs, the woven tumang sago sheath is used for seats, and the sago stems are used for firewood. There are 4 types of processed sago flour products, namely Papeda, Pompom, Sinoli, and Jepa-jepa, and based on basic ingredients, they can be divided into 2 main groups: raw (wet) and dried sago flour.